2019
DOI: 10.5812/semj.85190
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Expression, and Purification of p28 as a Cell-Penetrating Peptide ‎with Anticancer Effects on Burkitt’s Lymphoma Cell Line

Abstract: Background:The p28 is a small-sized cell-penetrating peptide derived from bacterial protein azurin and can function as a cancerspecific anti-proliferative agent. It can penetrate cancer tissues easily without involving the immune system, and increase the intracellular concentration of p53. Objectives: In this study, we have expressed and purified recombinant p28, then evaluated its anti-proliferative and pro-apoptotic effects on Raji cancer cell line. Methods: The p28 gene was amplified and cloned into pTZ57R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…To date, the only bacteriocin to enter phase I of a clinical trial is azurin-p28 peptide, which is a drug used in chemotherapy treatment and it demonstrated substantial activity in preclinical pharmacological studies [ 39 , 40 ]. Preclinical research supported the evaluation of this compound in a clinical setting, and azurin-p28 was observed to show selective cytotoxicity to cancer cells and inhibited cancer cell growth via the induction of apoptosis and inhibition of cell proliferation [ 78 , 79 ]. The primary goal of a two-part registered phase I clinical study (NSC745104) was to observe and determine the optimal safe therapeutic dose and potential adverse effects of azurin-p28 in treating adult patients with solid tumours and pediatric patients with advanced or recurring CNS malignancies by inhibiting p53 ubiquitination [ 39 , 40 ].…”
Section: Gut Microbial Metabolites and Clinical Research In Breast Ca...mentioning
confidence: 99%
“…To date, the only bacteriocin to enter phase I of a clinical trial is azurin-p28 peptide, which is a drug used in chemotherapy treatment and it demonstrated substantial activity in preclinical pharmacological studies [ 39 , 40 ]. Preclinical research supported the evaluation of this compound in a clinical setting, and azurin-p28 was observed to show selective cytotoxicity to cancer cells and inhibited cancer cell growth via the induction of apoptosis and inhibition of cell proliferation [ 78 , 79 ]. The primary goal of a two-part registered phase I clinical study (NSC745104) was to observe and determine the optimal safe therapeutic dose and potential adverse effects of azurin-p28 in treating adult patients with solid tumours and pediatric patients with advanced or recurring CNS malignancies by inhibiting p53 ubiquitination [ 39 , 40 ].…”
Section: Gut Microbial Metabolites and Clinical Research In Breast Ca...mentioning
confidence: 99%
“…In addition to the cancer cell lines listed above, the preferential entry and anti-proliferative effect of p28 are exhibited on other human cancer cell lines including ovarian cancer cells (SK-OV3 adenocarcinoma and ES-2 ovarian), fibrosarcoma (HT1080), leiomyosarcoma (HTB-88), osteosarcoma (TE85), and rhabdomyosarcoma (RD); pancreatic cancer (MIA-Paca2); Burkitt's lymphoma cell line (Raji and HEK-293); and neuroblastoma (IMR-32 (p53 wt ), and SK-N-BE2 (p53 mut ) (21,28,70,73).…”
Section: P28 and Other Cancer Cell Linesmentioning
confidence: 99%
“…The cancer cell deficiencies categorized into two types which including loss-of-function alterations affecting tumor genes and gain-of-function alterations affecting oncogenes (Teh & Fearon 2020 ). The cancer treatment modalities which are reported, including surgery, radiation therapy, and systemic treatment, as well as chemotherapy, targeted therapy, hormonal therapy, and immunotherapy (Abuei et al 2019 ; Miller et al 2019 ; Pirouzfar et al 2020 ). Although radio- and chemotherapy are the most common and non-invasive cancer treatment methods, it can cause serious damage to the normal cells (Mortezaee et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%